The art of racing in the rain : a novel - Stein, Garth (New York : Harper, 2008)
Nearing the end of his life, Enzo, a dog with a philosopher's soul, tries to bring together the family, pulled apart by a three year custody battle between daughter Zoe's maternal grandparents and her father Denny, a race car driver.
Donated by Farhana Zahir, Assistant Professor, BRAC Business School
Keywords: Dogs -- Fiction; Automobile racing drivers -- Fiction; Experimental fiction; Fiction